Pengenalan Bahasa Inggris di SDN Sugerkidul 3 Melalui Program English Time - Abdul Wahid; H. P., Agustin,; Abdul Rohim, Muhamat; Ade Permana, Angga; Baharudin, Baharudin; Khairna, Almas; Avia Zulita, Nur; Labibah, Balgis; Alifandi Habi Saleh, Geo; Muqsitoh Alfatah, Aysha; Qurnia Wati , Novi; Maryam , Siti; Akbar Ramadani , Feril; Fighur Firmansyah , Moh.; Azizah , Nurdiana; Imamah Izzatul M , Nur (JURNAL PENGABDIAN MASYARAKAT (JPM), 2024)
In the current era of globalization, almost all daily activities have begun to include the use of English, so it is considered necessary to have English language skills. Seeing this condition, English learning began to be given at a low level in formal education, namely elementary school. The same is the case with the English Time activities implemented at SDN Sugerkidul 3 by the Jember Collaborative KKN Group 220. This activity was carried out with the aim of introducing basic knowledge in English to students of SDN Sugerkidul 3. This research was conducted using descriptive qualitative methods because researchers try to describe the phenomena in the field broadly and thoroughly. Based on several considerations that have been made, this English Time activity is implemented using poster media and songs to make it easier for students to absorb and understand the learning provided during the activity. The media posters and songs are also expected to be used regularly and continuously by SDN Sugerkidul 3 itself. This English Time activity was also carried out because English is a subject that has just been added to the learning curriculum at SDN Sugerkidul 3. So this activity was chosen to make it easier for SDN Sugerkidul 3 to introduce this new subject. Keywords : English Time, Poster Media, Song Media